Peningkatan Minat dan Prestasi Bahasa Inggris Siswa melalui Project Based Learning dengan Media Komik - Karmila, Karmila (Universitas Muhammadiyah Magelang, 2018)
The objective of this research is to increase students’ interest and achievement in English subject through Problem Based Learning. The sample is 31 students of X MC. It was conducted in August until November 2017. The data were considered from learning process and their scores gathered through classroom observation and tests. The results show that (1) PBL seemed appropriate to be applied in English learning of Class X MC; (2) students enthusiastically took a part in learning; and (3) students’ average scores increased from 56,57 in cycle I to 82,26 in cycle II. It can be concluded that the use of Problem Based Learning Model can increase the students’ interest and achievement of English subject.